Worlds apart - Riley, James, 1977- (Riley, James, 1977- Story thieves, 2018)
After Nobody destroys the connection between fictional and nonfictional worlds, causing nonfictional people to lose their imaginations, Owen and Bethany must risk everything to save multiple realities.